A Analisis Faktor-Faktor Yang Berhubungan Dengan Kejadian Berat Badan Lahir Rendah Di Kabupaten Mesuji Tahun 2022 - Rini Iwan Lestari; Dewi Rahayu; Endang Budiati; Sugeng Eko Irianto; Aila Karyus (PT.Mantaya Idea Batara, 2023)
According to WHO (2020) 35.5% of infant deaths are caused by low birth weight (LBW). In Indonesia, 79.1% of deaths occur in infants. In Mesuji District, there were 97 cases of LBW from 2,786 births. The research objective was to analyze the factors associated with the incidence of low birth weight in Mesuji District. This type of quantitative research, with a case control approach design. study population, all newborns were 2,907 babies. The research sample is 124 respondents. The sampling technique was purposive sampling. The method of collecting data is by observing checking medical record books and MCH books. Based on statistical tests, it was found that there was a relationship between maternal age (p-value 0.035, OR 2.476), ANC visits (p-value 0.000, OR 24.537), maternal nutritional status (p-value 0.001, OR 4.253), and anemia (p-value 0.010 OR 3.133) with the incidence of low birth weight in Mesuji District.The ANC visit variable became the dominant variable (p-value 0.000 OR 22.624) with the incidence of LBW. Suggestions, it is hoped that the health office can facilitate increased collaboration in improving education and community empowerment in order to create public understanding of health behavior and optimal utilization of health services.